Reduced Treatment Sensitivity of SARS-CoV-2 After Multigenerational Human-to-Human Transmission - Wang, Qiang; Yang, Tong; Wang, Yang (Frontiers in Physics, 2020)
COVID-19 due to SARS-CoV-2 virus infection has been characterized as a pandemic by World Health Organization. As of July 16, 2020, the virus has caused 13643353 confirmed cases and 583033 deaths in over 200 countries through international or regional population flow, which seriously threatens global public health security. At present, there is still no vaccine or specific drug available for the virus, therefore, epidemiological prevention and control is crucial to block the further spread of the disease. Here, based on the public information of COVID-19 of Qingdao, Shandong Province, China, we analyzed the epidemiological characteristics and treatment effects of 60 confirmed cases. It was found that the hospitalization time of patients imported from Wuhan or infected by Wuhan patients was significantly shorter than that of those imported from other regions and those infected by them. In addition, for patients in the transmission chain directly associated with Hubei Province, the earlier transmission generation, which refers to the imported patients (G0) and the first-generation infections (G1), was associated with reduced cure time. Therefore, we speculate that the treatment sensitivity of SARS-CoV-2 has been decreasing within interpersonal transmission in the early stage of this epidemic.